Przedmiot i źródła nadziei chrześcijańskiej w listach Pawłowych - Lasek, Paweł (2025)
The purpose of this paper is to analyze the theme of hope in the Corpus Paulinum. The Apostle to the Gentiles uses the term "hope" frequently, in both its noun and verb forms, understanding it as the expectation of something in the future. While he sometimes relates this expectation to temporal realities, he also distinguishes another kind of hope—Christian hope—which refers to eternity. The object of this hope is described in various ways, yet it can be summed up as eternal life in heaven. This Christian hope is grounded above all in the person and work of Jesus Christ—a work that has already taken place (and is thus a fact) and which, for the one who accepts it in faith, becomes the foundation for expecting its fulfillment in the sphere of eternity. The community of such believers constitutes Christ’s Church of the New Covenant, the temple and sphere of the Holy Spirit’s activity. The Spirit’s person and work serve as a "deposit" guaranteeing believers’ future and eternal destiny, and thus as another source of their hope regarding life after death. In addition, this hope rests on the enduring and imperishable character of Christ’s sacrifice and the New Covenant between God and humanity established in Him, as well as on God’s revelation in the incarnation of the Son and in the Gospel, which imparts to believers knowledge of the spiritual and eternal reality.
Celem artykułu jest analiza Corpus Paulinum pod kątem tematu nadziei. Apostoł Narodów stosunkowo często posługuje się terminem „nadzieja”, zarówno w formie rzeczownikowej, jak i czasow-nikowej. Nadzieja jest rozumiana jako oczekiwanie czegoś, co ma się wypełnić w przyszłości. Paweł Apo-stoł kilkakrotnie odnosi to oczekiwanie do rzeczywistości doczesnej, ale wyróżnia także inną, „jedną” nadzieję – nadzieję chrześcijańską, odnoszącą się do wieczności. Przedmiot tej nadziei bywa różnie nazy-wany, lecz wszystkie określenia sprowadzają się do jednego: jest nim życie wieczne w niebie. Nadzieja ta opiera się przede wszystkim na osobie i dziele Jezusa Chrystusa – dziele już dokonanym, które jest fak-tem, i które dla człowieka przejmującego je z wiarą stanowi podstawę oczekiwania pełni jego skutków w wieczności. Wspólnota tych ludzi tworzy Kościół Chrystusowy Nowego Przymierza, który jest świąty-nią i polem działania Ducha Świętego, którego osoba i działanie są „zadatkiem” przyszłego i wiecznego losu wierzących, a przez to kolejnym źródłem ich nadziei, co do ich losu po śmierci. Dodatkowo nadzieja opiera się na trwałości i nieprzemijalności charakteru ofiary Chrystusa i zawartego w Nim Nowego Przy-mierza między Bogiem a ludzkością oraz na objawieniu się Boga we wcieleniu Swojego Syna i w Jego Ewangelii, co daje wierzącym poznanie rzeczywistości duchowej i wiecznej.
Keywords: Holy Spirit; Jesus Christ; Paul the Apostle; Eternal Life; Hope; nadzieja; życie wieczne; Corpus Paulinum; Paweł Apostoł; Jezus Chrystus; Duch Święty